2020
DOI: 10.1186/s12933-020-0989-8
|View full text |Cite
|
Sign up to set email alerts
|

The atherogenic index of plasma plays an important role in predicting the prognosis of type 2 diabetic subjects undergoing percutaneous coronary intervention: results from an observational cohort study in China

Abstract: Background Many studies have reported the predictive value of the atherogenic index of plasma (AIP) in the progression of atherosclerosis and the prognosis of percutaneous coronary intervention (PCI). However, the utility of the AIP for prediction is unknown after PCI among type 2 diabetes mellitus (T2DM). Methods 2356 patients with T2DM who underwent PCI were enrolled and followed up for 4 years. The primary outcome was major cardiovascular and cerebrovascular adverse events (MACCEs), considered to be a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
79
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 37 publications
6
79
2
Order By: Relevance
“…Qin Z, et al retrospectively enrolled 2356 T2DM patients who underwent PCI and followed them for 4 years. They found that AIP was an independent predictor of major cardiovascular and cerebrovascular adverse events including cardiac death, MI, repeated revascularization, and stroke, regardless of clinical presentation [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qin Z, et al retrospectively enrolled 2356 T2DM patients who underwent PCI and followed them for 4 years. They found that AIP was an independent predictor of major cardiovascular and cerebrovascular adverse events including cardiac death, MI, repeated revascularization, and stroke, regardless of clinical presentation [27].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, we presume that AIP can better re ect the lipid characteristics of diabetic patients. Recently, AIP has been demonstrated to be associated with CV morbidity and mortality in general population and different patients groups [17][18][19][20][21][22][23][24][25][26][27][28]. However, the prognostic impact of AIP on admission among T2DM patients with ACS undergoing PCI has not been exclusively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidences now clearly indicate that patients with CID are prone to cardiovascular diseases (CVD) such as cerebrovascular accident (CVA), coronary artery disease (CAD), and thromboembolic diseases [10][11][12]. Notably, atherogenic index of plasma (AIP), which is calculated based on serum TG and HDL-cholesterol, is one of the laboratory indices indicating atherogenic status, and this has been used to assess the extent of dyslipidemia and predict the potential of developing CVA and CAD in various medical conditions [13][14][15]. Given that patients with CID are more often affected by CVDs than in healthy subjects and that increase of TG and decrease of HDL-cholesterol is present in those with chronic in ammation, it is possible that AIP is elevated in AAV patients and is associated with CVA and CAD.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that AIP was a useful marker for predicting adverse cardiovascular events in type 2 diabetic patients undergoing percutaneous coronary intervention (PCI) [6]. However, the association between AIP and survival among patients with type 2 diabetes and ACS remains undetermined.…”
Section: Introductionmentioning
confidence: 99%